Erratum: Addendum to Zootaxa 4612 (3): On some new and old soft scale insects (Hemiptera: Coccomorpha: Coccidae) from Africa, with description of a new Coccus species and introduction of a new genus by B. Łagowska and Chris J. Hodgson. - Łagowska, Bożena; Hodgson, Chris J. (Zootaxa, 2019)
Due to an oversight, the depositories of the new species, Coccus giliomeei Łagowska & Hodgson, and of the new material of Coccus rhodesiensis (Hall) collected in the Transvaal, South Africa, was omitted from the manuscript.  Both lots of slides will be deposited in SANC, The South African National Collection of Insects, Pretoria, South Africa.